Performance Assessment in a Heat Exchanger Tube with Opposite/Parallel Wing Twisted Tapes - S. Eiamsa-ard; M. Pimsarn; C. Thianpong (Advances in Mechanical Engineering, 2015)
The thermohydraulic performance in a tube containing a modified twisted tape with alternate-axes and wing arrangements is reported. This work aims to investigate the effects of wing arrangements (opposite (O) and parallel (P) wings) at different wing shapes (triangle (Tri), rectangular (Rec), and trapezoidal (Tra) wings) and on the thermohydraulic performance characteristics. The obtained results show that wing twisted tapes with all wing shape arrangements (O-Tri/O-Rec/O-Tra/P-Tri/P-Rec/P-Tra) give superior thermohydraulic performance and heat transfer rate to the typical twisted tape. In addition, the tapes with opposite wing arrangement of O-Tra, O-Rec, and O-Tri give superior thermohydraulic performances to those with parallel wing arrangement of P-Tra, P-Rec, and P-Tri around 2.7%, 3.5%, and 3.2%, respectively.